The Role of Soft Skills and Organizational Unfairness between Leadership Style and Employee Performance: A Quantitative Study in Educational Institutes of Pakistan - Khan, Kamran; Gul, Mahvia (iRASD Journal of Management, 2022)
Thoughts, strategies, beliefs, and philosophies are continually evolving and changing. In this era of change and growth, leaders have the greatest impact on the success and long-term viability of all organizations and institutions, as well as the formation and maintenance of organizational culture (Robbins & Judge, 2012). Furthermore, the same holds true for educational institutions. Therefore, this study is interested in identifying the effect of leadership styles on employee performance, focusing on the mediating role of soft skills and the moderating role of organizational unfairness. A quantitative method was adopted, and the data of 184 teachers was collected by a higher educational institute. The study has used a cross-sectional research design by using the convenience sampling technique. SMART PLS version 22 data analysis reveals that transactional and transformational leadership styles have a significant positive relationship with employee performance via the mediating role of soft skills. Further organizational unfairness has negatively moderated the relationship between transactional and transformational leadership styles and employee performance. The present study is useful for building employee performance by employing various soft skills and leadership styles and reducing the environment of organizational unfairness. This research could pave the way to improving employee and management readiness to face the 4.0 education era. Limitations and future recommendations are discussed.